Nilai Psikologi Tokoh Utama Dalam Novel “Aku Tak Membenci Hujan” Karya Sry Puji Hartini - Melsa Lianti Batuk; Sanhedri Boimau; John Darwis Fallo; Ona Diana Bani (KAMPUS AKADEMIK PUBLISING, 2026)
The issues raised in this study are (1) what is the psychological condition of the main character, and (2) what are the psychological values found in the novel